2022
DOI: 10.1108/jima-03-2022-0092
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ awareness and loyalty in Indonesia banking sector: does emotional bonding effect matters?

Abstract: Purpose This study aims to examine the relationship between emotional bonding (e.g. brand love, brand commitment and brand trust) and consumers’ awareness and consumers loyalty to conventional and Islamic banking products in Indonesia. Design/methodology/approach The sample consists of 585 Muslim and bank consumers obtained through a survey study and using structural equation modeling to test the research hypotheses. Findings The empirical results indicate that brand love, commitment and trust have signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 62 publications
(190 reference statements)
1
14
1
Order By: Relevance
“…This is as a result of the business offering value and a remedy. This result opposite with prior studies by Karim et al, (2022) and Suhartanto et al, (2019) who found that brand play important role on consumers' loyalty. Table 4 shows the results of the research hypotheses.…”
Section: Structural Modelcontrasting
confidence: 99%
See 4 more Smart Citations
“…This is as a result of the business offering value and a remedy. This result opposite with prior studies by Karim et al, (2022) and Suhartanto et al, (2019) who found that brand play important role on consumers' loyalty. Table 4 shows the results of the research hypotheses.…”
Section: Structural Modelcontrasting
confidence: 99%
“…Moreover, customers' brand loyalty significantly and favourably influences the relationship between consumer pleasure and loyalty. This result confir preliminary studies which concluded consumers' brand awareness and attitude play important role in mediating the relationship between consumers' satisfaction and loyalty (Karim et al, 2022;Mursid & Wu, 2022;Othman et al, 2021;Suhan et al, 2022). It meas that consumers' emotional bonding play important role to keep company going concern and competitive advantage.…”
Section: Mediating Effectsupporting
confidence: 48%
See 3 more Smart Citations